Fuzzification of the Dual B-Algebra (European Journal of Pure and Applied Mathematics, 2022)
This paper introduces the fuzzification of the dual B-algebra and presented some of its related properties. A characterization of a fuzzy (normal) dual B-algebra is also investigated.
Keywords: dual algebra; categories of algebra; fuzzy algebraic structure